THE EFFECT OF ELECTRICAL STIMULATION OF WORKING MUSCLES ASSOCIATED WITH SPECIAL EXERCISES IN DEVELOPING STRENGTH FOR THE LEGS AND REDUCING THE SPIN TIME IN YOUNG SWIMMERS - Ammar Ali Ismael Al-Tameemi (Proximus Journal Publishing, 2025)
The study sought to ascertain the impact of electrical stimulation of active muscles in conjunction with specialised exercises on enhancing leg strength and decreasing rotation time in young swimmers. The researcher employed an experimental methodology involving a total sample of 11 participants from the youth category, aged 15 to 18 years, representing 50% of the original population from the Amara Sports Club. The statistical analysis was conducted using the SPSS-24 software. Based on the findings of the researcher, it was determined that electromuscular planning is an effective and precise method for assessing muscle strength that influences performance. Furthermore, the implementation of specialised exercises and electrical stimulation enhances swimming rotation time, leg muscle strength, stability in the broad jump, wall push-off duration, and 50 m swimming time, thereby improving muscular balance on both sides of the body, which positively impacts performance and achievement, as concluded by the researcher. He proposed numerous suggestions, emphasising the necessity of utilising contemporary equipment to identify problems in muscular function, particularly the electromyography device for electromuscular assessment. The equilibrium of maximum muscular strength on both sides of the body during pressure elevation from a supine position necessitates the implementation of specialised exercises and electrical stimulation. This approach aims to establish a training regimen that integrates the benefits of both modalities to enhance maximum strength and improve muscular balance in swimmers.
Keywords: Electrical Stimulation; Muscles; Special Exercises